2017
DOI: 10.1016/s2095-3119(17)61679-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background analysis and breed evaluation of Yiling yellow cattle

Abstract: Traditionally, Chinese indigenous cattle is geographically widespread. The present study analyzed based on genome-wide variants to evaluate the genetic background among 157 individuals from four representative indigenous cattle breeds of Hubei Province of China: Yiling yellow cattle (YL), Bashan cattle (BS), Wuling cattle (WL), Zaobei cattle (ZB), and 21 individuals of Qinchuan cattle (QC) from the nearby Shanxi Province of China. Linkage disequilibrium (LD) analysis showed the LD of YL was the lowest (r 2 =0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Such adaptation may be of relevance in particular for outdoor grazing animals (Kim et al, 2017). The GTPase activity cluster found in Jenoubi breed, which plays a significant role in inflammatory reaction following nematode infection (Huang et al, 2007; Kim et al, 2015), and in relation to milk and fertility traits (Kasarapu et al, 2017), has also been found in Yiling yellow Chinese cattle (Ling et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Such adaptation may be of relevance in particular for outdoor grazing animals (Kim et al, 2017). The GTPase activity cluster found in Jenoubi breed, which plays a significant role in inflammatory reaction following nematode infection (Huang et al, 2007; Kim et al, 2015), and in relation to milk and fertility traits (Kasarapu et al, 2017), has also been found in Yiling yellow Chinese cattle (Ling et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…It was formerly selected as a draught animal, but now this breed and its hybrids are bred only for beef production, especially for high marbling beef. A previous study [2] evaluated its genetic background. Furthermore, the finishing performance of YL cull cows was evaluated in our previous feeding experiment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Spanish beef cattle breeds [36], Canchim [37], Chinese Yiling yellow cattle [38] and many other indigenous and exotic cattle breeds raised in different countries worldwide [39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%